Exploring Household Financial Self-Efficacy Amid MCO - Hway-Boon Ong (INTERNATIONAL RESEARCH JOURNAL OF BUSINESS STUDIES, 2022)
The outbreak of the covid-19 pandemic had forced economies to implement movement restrictions that resulted in income shock to households.  This study aims to gauge the impact of income shock due to movement control order (MCO).   This study examined the factors that affect Malaysian household financial self-efficacy due to movement restrictions.  A survey was conducted online from 1 April 2020 to 30 June 2020 to gather responses from households.  Data collected were analyzed using the KMO sampling adequacy test, Bartlett's test, reliability, and factor analysis.  More than 46% of the respondents’ income was significantly decreased or somewhat decreased due to MCO.  Financial tools, lifestyle adaptation, contingency plans, and realization of the impact of MCO had significantly affected household financial efficacy.